Teaching Lexicography as a University Course: Theoretical, Practical and Critical Considerations - Prćić, Tvrtko (Lexikos, 2020)
This paper offers an account of a university course in Lexicography, designed particularly for advanced EFL students. The discussion and accompanying material derive from around fifteen years of the author's experience in developing and teaching this course. The aims of the paper are twofold: firstly, to draw attention to the fact that lexicography today is no longer just 'the art and craft of' dictionary making of yesteryear but a fully-fledged applied linguistic discipline, with its own theory, methodology and practice, some of which is teachable as a dedicated academic subject; and secondly, to encourage the teaching of practical and theoretical lexicography to university students by putting forward concrete proposals. The exposition is divided into five parts, as follows: Section 1 brings some opening remarks, including that on the scientific status of lexicography; Section 2 reviews theoretical aspects regarding the design of this course; Section 3 describes practical aspects regarding the implementation of the course; Section 4 examines critical aspects regarding the evaluation of the course; and Section 5 recapitulates the main points of the paper and projects the modifications to the course in the future.